Analisis Keterlaksanaan RPP Versi Daring Kelas XI Materi Jaringan Tumbuhan Di MAN 3 Jombang - Fatmawati, Widia (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2023)
ABSTRACT This study was conducted to find out how the analysis of the implementation of online lesson plans for class XI on plant tissue material, the results of which will be described qualitatively. The type of research used is case study research that is qualitative (qualitative case study). The research method used in this research is descriptive. From the results of the analysis of RPP at meetings 4-5, it was found that 76.1% with the appropriate criteria. Meanwhile, at the 6th meeting, it was obtained 77.7% with the appropriate criteria. After conducting research on the analysis of the implementation of online lesson plans for class XI plant tissue material at MAN 3 Jombang, the authors can draw conclusions, namely, the implementation of online lesson plans in the biological learning process of plant tissue material is in accordance with the percentage at meetings 4-5 of 76.1% and meeting 6 of 77.7%. The Biology subject teacher for class XI MIPA 8 material on plant tissue at MAN 3 Jombang has carried out learning according to the online learning lesson plan. The suitability of the GPA with cognitive, affective, and psychomotor assessments in the study was appropriate. KEYWORDS: RPP analysis, online learning, plant tissue   ABSTRAK Penelitian ini dilakukan untuk mengetahui bagaimana analisis keterlaksanaan RPP daring kelas XI materi jaringan tumbuhan yang hasilnya akan dideskripsikan secara kualitatif. Jenis penelitian yang digunakan adalah penelitian studi kasus yang bersifat kualitatif  (qualitative case study). Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif. Dari hasil analisis RPP pada pertemuan 4-5 didapatkan sebesar 76,1 % dengan kriteria sesuai. Sedangkan pada pertemuan 6 didapatkan sebesar 77,7 % dengan kriteria sesuai. Setelah melakukan penelitian tentang analisis keterlaksanaan RPP daring kelas XI materi jaringan tumbuhan di MAN 3 Jombang, maka penulis dapat mengambil kesimpulan yaitu, keterlaksanaan RPP daring pada proses pembelajaran biologi materi jaringan tumbuhan sudah sesuai dengan presentase pada pertemuan 4-5 sebesar 76,1 % dan pertemuan 6 sebesar 77,7 %. Guru mata pelajaran Biologi kelas XI MIPA 8 materi jaringan tumbuhan di MAN 3 Jombang telah melaksanakan pembelajaran sesuai dengan RPP pembelajaran daring. Kesesuaian IPK dengan penilaian kognitif, afektif, dan psikomotorik dalam penelitian sudah sesuai. KATA KUNCI: RPP, Pembelajaran daring, jaringan tumbuhan